Microwave-Assisted Metathetic Synthesis of Er3+/Yb3+ Co-Doped BaMoO4 Particles and Their Upconversion Photoluminescence Properties - Sung Lim, Chang (Asian Journal of Chemistry, 2013)
Er3+ doped BaMoO4 (BaMoO4:Er3+) and Er3+/Yb3+ co-doped BaMoO4 (BaMoO4:Er3+/Yb3+) particles were successfully synthesized by a cyclic microwave-assisted metathetic method showing a fine and homogeneous morphology with particle sizes of 0.5-1 μm. At excitation at 980 nm, BaMoO4:Er3+ and BaMoO4:Er3+/Yb3+ particles exhibited a strong 525-nm emission band and a weak 550-nm emission band in the green region. The UC intensity of BaMoO4:Er3+/Yb3+ particles was higher than that of the BaMoO4:Er3+ particles. The Raman spectrum of BaMoO4:Er3+/Yb3+ particles indicated the detection of additional peaks at higher frequencies (390 and 505 cm-1) and at lower frequencies (218 and 255 cm-1).